2021
DOI: 10.26508/lsa.202000999
|View full text |Cite
|
Sign up to set email alerts
|

iNKT cells coordinate immune pathways to enable engraftment in nonconditioned hosts

Abstract: Invariant natural killer T (iNKT) cells are a conserved population of innate T lymphocytes that interact with key antigen-presenting cells to modulate adaptive T-cell responses in ways that can either promote protective immunity, or limit pathological immune activation. Understanding the immunological networks engaged by iNKT cells to mediate these opposing functions is a key pre-requisite to effectively using iNKT cells for therapeutic applications. Using a human umbilical cord blood xenotransplantation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…To replicate our clinical observational study, we used a human xenogeneic transplant model wherein we transplanted various human graft tissues into immunodeficient mice ( 31 , 59 , 60 ). As we have published previously, xenogeneic GVHD (xeno-GVHD) is dose dependent with each human graft source having its own median lethal dose (LD 50 ) and that the development of xeno-GVHD is not donor dependent ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…To replicate our clinical observational study, we used a human xenogeneic transplant model wherein we transplanted various human graft tissues into immunodeficient mice ( 31 , 59 , 60 ). As we have published previously, xenogeneic GVHD (xeno-GVHD) is dose dependent with each human graft source having its own median lethal dose (LD 50 ) and that the development of xeno-GVHD is not donor dependent ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…To replicate our clinical observational study, we utilized a human xenogeneic transplant model wherein we transplanted various human graft tissue into immunodeficient mice 31,54,55 . As in our observational clinical study, we observed the presence of DPTs, which were not present in the starting healthy graft tissue, primarily developing in mice that would later develop lethal xenogeneic GVHD (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
“…To replicate our clinical observational study, we utilized a human xenogeneic transplant model wherein we transplanted various human graft tissue into immunodeficient mice 31,59,60 . As we have published previously, xenogeneic GVHD (xeno-GVHD) is dose-dependent with each human graft source possessing their own LD 50 dose and that the development of xeno-GVHD is not donor dependent 59 .…”
Section: Introductionmentioning
confidence: 99%
“…We also used a xenotransplantation model of hematopoietic engraftment to investigate the impact of the human iNKT-monocyte pathway in vivo . The addition of allogeneic adult iNKT cells to human cord blood mononuclear cell grafts resulted in dramatically improved engraftment, which was due to iNKT cells inducing cord blood monocytes to secrete prostaglandin E 2 , which potently suppressed T cell IFN-γ production ( 44 ). Since hematopoietic engraftment is suppressed by excessive IFN-γ ( 45 ), this analysis shows that human iNKT cells can engage powerful regulatory pathways that limit adverse effects of human T H1 activation in vivo .…”
Section: How Are the Anti-inflammatory Effects Of Inkt Cells Mediated?mentioning
confidence: 99%
“…Perhaps more importantly, polyfunctional human iNKT cells show a hierarchy of cytokine production in response to TCR stimulation that does not neatly segregate into clear T H1 or T H2 patterns. Weak TCR stimulation of human iNKT cells preferentially induces production of IL-3, GM-CSF, and IL-13, with increasing stimulation leading first to IFN-γ, then IL-4, then IL-2 ( 44 , 103 , 104 ) ( Figure 2D ). Secondary induction of NK cell IFN-γ secretion was associated with activation of human iNKT cells by strong TCR agonists ( 104 ).…”
Section: What Determines the Nature Of The Functional Response Mediat...mentioning
confidence: 99%